PENGARUH PENYULUHAN KESEHATAN REPRODUKSI TERHADAP PENGETAHUAN TENTANG PERILAKU SEKSUAL REMAJA - Herselowati Herselowati; Nita Tri Wahyuni; Mera Marhamah (NHM PRESS, 2023)
The impact of the lack of knowledge of adolescents on reproductive health is that many adolescents are already sexually active. The purpose of this study was to find out how big the influence of counseling on reproductive health is on changes in adolescent knowledge in Susukan Village, East Jakarta in 2023. This research is a type of quasi-experimental research with a one group pre test and post test design carried out in one group only without a comparison group aims to see the Effect of Counseling About Reproductive Health on Adolescent Knowledge. The sample in this study amounted to 95 students. The research instrument used a questionnaire filled out by teenagers. The independent variable in this study that was studied was the knowledge of adolescents. The results showed that of the 95 adolescents who attended counseling about reproductive health, prior to counseling it was shown that the frequency of knowledge about adolescent reproductive health was mostly low, namely 54 respondents (56.8%) and the remaining 41 respondents who had high knowledge. And after counseling the results were obtained, out of 95 respondents there were 87 respondents who had good knowledge (91.6%) and the remaining 8 respondents (8.4%) had low knowledge. The results of the Mc.Nemar test showed that before and after counseling interventions were carried out on adolescent reproductive health with the test results obtained that there were significant differences in adolescent knowledge with a p value of 0.000 where <0.05. The conclusion from this study was that the knowledge of adolescents prior to health education about reproductive health was lacking, with the number of respondents 95 being 72.78%. The effectiveness of health counseling using the lecture method and also presentation of power points towards increasing reproductive health knowledge in adolescents is 79.73.